2005
DOI: 10.1158/0008-5472.can-05-2446
|View full text |Cite
|
Sign up to set email alerts
|

Short Hairpin RNA–Mediated Inhibition of Matrix Metalloproteinase-1 in MDA-231 Cells: Effects on Matrix Destruction and Tumor Growth

Abstract: Increased matrix metalloproteinase-1 (MMP-1) expression is associated with advanced stages of breast cancer and may be a predictive marker for the development of invasive disease. In this report, we used short hairpin RNA (shRNA) molecules to investigate whether MMP-1 production in MDA-231 breast cancer cells contributed to the degradation of a collagen matrix or tumor formation in nude mice. We created two groups of MDA-231 cell lines. MDA-231 cells containing a vector producing shRNA specific for MMP-1 had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 37 publications
(48 reference statements)
3
81
0
Order By: Relevance
“…The collagen degradation assay was performed as previously described (24,25). Briefly, fibrillar collagen preparations were made from Vitrogen 100 bovine type I collagen (Cohesion Technologies, Palo Alto, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The collagen degradation assay was performed as previously described (24,25). Briefly, fibrillar collagen preparations were made from Vitrogen 100 bovine type I collagen (Cohesion Technologies, Palo Alto, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…This did not result in the liberation of medium (data not shown). Other studies have shown that when the 1-ml collagen plug is fully degraded, ϳ2 ml of total medium can be recovered (25).…”
Section: Specific Inhibition Of Mmp-1 and Mmp-13 Production By Pretrementioning
confidence: 97%
See 3 more Smart Citations